Pengembangan Video Pembelajaran Kubus dan Balok dengan Model Project Based Learning (PjBL) Berbantuan Geogebra - Harry Trisakti Kunrade; Victor R. Sulangi; Derel F. Kaunang (JTMT: Journal Tadris Matematika, 2023)
Harry Trisakti Kunrade. 18504084. development of cube and Block studying movies with Geogebra Assisted project based learning (PjBL) models in class VIII SMP Negeri Satap Molobog. Mathematics Departement. Faculty of Mathematics, Natural and Earth Sciences. Manado Dtate University. Tondano. 2023. This studies is motivated through problems determined in learning mathematics that are observed from various factors, one in every of which is the dearth of use of media. The purpose of this observe changed into to supply mastering video media products on cube and block cloth with a geogebra-assisted task primarily based mastering (PjBL) model in magnificence VIII SMP Negeri Satap Molobog which is valid, practical and effective. The ADDIE development methodology (Analysis, Design, Development, Implementation, and Evaluation) is used in this form of study, which is referred to as research and development (R&D). 16 kids from SMP Satap Negeri Molobog's eighth grade served as the study's participants. Interviews, questionnaires, learning assessment worksheets in the form of learning implementation plans (RPP), student worksheets (LKPD), and outcomes evaluation questions were all included in the study tools and documentation, data analysis to create learning media products, and knowledge of the valid, prtical, and effective of the generated goods. the share of validity of the consequences of the media professional's evaluation became 92.374% and the share of the result of the material professional's evaluation turned into 94.78% with a completely valid category. For the praticality percent of the media visible from the teacher's response of 96.36% and for student responses 94.625% within the very good category. This evolved learning media meets the effective standards based on the proportion of classical getting to know completeness of 81.25%> 75% of students who are declared to have finished getting to know the use of the learning media used. In end, the academic video media developed is valid, practical, and effective for use in learning. Keywords: Studying Movies, Project Based Learning, Geogebra, Cube and Blocks.